Intermediation, Compensation and Collusion in Insurance Markets - Uwe Focht; Andreas Richter; Jörg Schiller (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
Recent events involving major insurance companies and insurance brokerage firms highlight substantial incentive problems in commercial and reinsurance markets where intermediation takes place. We show that in markets with informed as well as uninformed consumers and heterogeneous risk profiles intermediation has the potential to improve social welfare. However, since intermediation reduces insurers' market power, incentives for tacit collusion are higher compared to markets without intermediation. A controversial matter in the discussion concerning insurance intermediation is the issue of compensation customs. Our analysis provides explanations for the counterintuitive observation that brokers are usually compensated by insurance companies. The rationale for the latter is the fact that a fee paid by uninformed consumers limits the insurers' ability to extract rents from informed consumers.
urn:nbn:de:bvb:19-epub-1647-8
Keywords: D83; G22; J33; 650; insurance; brokerage; collusion; compensation; information